[Memo from Kay Thomas to John Lyons re: the Indoor Safe Air Act of 1989] - KAY THOMAS (Tufts Archival Research Center, 2007)
Marginalia; Cover memo from Kay Thomas to John Lyons introducing attached agenda and testimonies of a hearing on the Indoor Safe Air Act of 1989. Focuses on David Schlein's testimony on behalf of the American Federation of Government Employees. Notes that Schlein highlighted over crowding and poor ventilation as the main causes of poor air quality. Lists media present.